Answer:
-9>x
Step-by-step explanation:
5(x+4)>2x-7
5x+20>2x-7
5x+20>2x-7
<u> +7 +7</u>
5x+27>2x
↓
5x+27>2x
<u>-5x -5x</u>
27>-3x
↓
<u>27>-3x </u>
-3 -3
= -9>x
9423
three goes into nine three times
which gives you zero then bring the four down
three goes into four one time then subtract four from three then that gives you one than bring the two down which makes twelve and three goes into twelve four times and 12 subtracted from twelve gives zero and then bring the three down and three goes into three 1 time so that equal zero
so in total the whole answer should be 3141
The y intercept and -4 and going down 2 and 1 right u til you reach the end of the graph
Answer:
30.56 yd²
Step-by-step explanation:
To determine the area of the composite shape, we need to:
- Divide the shape into two smaller "known" shapes (Refer to image).
- Determine the area of those "known" shapes.
- Add the area of the known shapes to obtain the area of the figure.
<u>Determining the area of shape 1 (Rectangle 1):</u>
⇒ Area of rectangle = Lenght × Breadth
⇒ = 2.1 × 4.8
⇒ = 10.08 yd²
<u>Determining the area of shape 2 (Rectangle 2):</u>
⇒ Area of rectangle = Lenght × Breadth
⇒ = 6.4 × 3.2
⇒ = 20.48 yd²
<u>Determining the area of the figure:</u>
⇒ Area of figure = Area of rectangle 1 + Area of rectangle 2
⇒ = 10.08 + 20.48
⇒ = 30.56 yd²